Computational modeling for evaluating the economic impact of airports on regional economies - Sartzetaki, Maria (Cranfield University, 2011)
Airports, as fundamental nodes of the air transport network, reflect the economic status of the region they serve and act as major engines of economic development, as was stated in ACI 2004. The impact of regional tourist airports on their region is more important due to the fact that there is a high interrelation between airports and tourism. A growing literature on this subject highlights the methods used to calculate the total effect of an airport on regional economy, and the difficulties entailed in such calculations. Τhe key objectives of this research are to develop an econometric assessment model based on a computational modelling concept that will estimate the economic impact of Regional Tourist Airports on Regional economy. The modelling framework is based on the Input Output Analysis concept and is in accordance with the theoretical principles of regional and national Economics, as well as all the reviewed models which have been developed globally, in order to assess the regional economic significance of airports and transportation projects. The case study of the research is the new airport in the Island of Crete in Greece, one of the most attractive tourist destinations in southeast Mediterranean. Conventional wisdom dictates the presentation of a Computational Input Output Model, appropriate for this purpose, in order to quantify the total value of the new airport operation in terms of jobs and income, at a regional and national level. The Economic impact that the Model will estimate includes four categories of impact: direct, indirect, induced and catalytic. The model outputs will measure these impacts in terms of Jobs, total Income and Total growth of GDP. The goal is to create a Model, which will be appropriate for application in relevant tourism regional airports, giving an essential tool in order to support decisions at the level of strategic planning, providing essential results about the impact of tourist airports developing a new airport and estimating the economic development.